Diversity and distribution of freshwater fishes at Sungai Muar, Kuala Pilah, Negeri Sembilan / Nur Hasyimah Ramli and Wan Nur Atilla Antasha Megat Asrul Hazaman - Ramli, Nur Hasyimah; Megat Asrul Hazaman, Wan Nur Atilla Antasha (Universiti Teknologi MARA, Negeri Sembilan, 2021)
Freshwater fishes are species that spend their entire live in either freshwater inland or brackish estuaries. The checklist of the fish species should be updated consistently to ensure their diversity is preserved. The study of diversity and distribution of freshwater fishes at Sungai Muar, Kuala Pilah, Negeri Sembilan was carried out on 14 and 15 March 2020 to identify the fish diversity and their development in Sg. Muar, Negeri Sembilan. Trawl (fish collections), weighing machine and ruler (morphometric observations) was used during experiment. Fish species found during this study include Oreochromis mossambicus (Family Cichlidae), Hemibagrus nemurus (Family Bagridae), Homaloptera tweediei (Family Balitoridae), Notopterus notopterus (Family Notopteridae), Oxyeleotris marmorata (family Eleotridae), and five species of Family Cyprinidae, which were Mystacoleucus marginatus, Osteochilus haseltii, Cyclocheilichthys apogon, Barbonymus schwanenfeldii and Hampala microlepidota. Fishes from family Cyprinidae was dominated the area with a total of 102 individuals found. The statistical analysis shows the diversity (H')=1.826, richness (R')=2.004 and evenness (E')= 0.5645 of freshwater fish at Sungai Muar, respectively. The most dominant species found was Mystacoleucus marginatus with 50 individuals and the least abundant species were Barbonymus schwanenfeldii, Homaloptera tweediei and Oxyeleotris marmorata with one individual only. The length-weight regression shows a positive allometric growth with 'b' value is higher than 3 at both stations; 3.0118 (Station 1) and 3.4409 (Station 2). It shows that the fish becomes heavier as its length increases. This data provides information about the fish habitat in Sungai Muar and can be used to update the checklist of fish species in Sg Muar. The data obtained provides information about the fish habitat in Sungai Muar which could be useful for the planning of fishing activities Other than that, it also important as a guideline for future research and conservation purposes especially in Negeri Sembilan.